Fatty acid composition of milk fat in milk of Tzigay sheep and their F2 cross-breeds with chios - Gerchev G.; Naydenova N.; Slavkova S.; Mihaylova G. (Biotechnology in Animal Husbandry, 2015)
The study was conducted on aggregate milk samples, which were taken every month during the milking period from Tzigay sheep and their F2 cross-breeds of Chios, raised in the conditions of the Central Balkan Mountain. The fat extraction of milk samples was done by the Rose-Gottlieb method. Fatty acid composition was determined on a gas chromatograph with flame ionization detector and capillary column. The aim of the study was to follow the changes in the composition of fatty acids in the milk fat of milk of Tzigay sheep and their F2 cross-breeds. The saturated fatty acids in milk of the two groups had high values during both consecutive years, as they varied from 67.05% in milk of Tzigay sheep in the second lactation up to 70.87% at their F2 cross-breeds. The content of myristic acid was correspondingly 8.22-8.88% at Tzigay sheep and 8.45-8.74% at their F2 cross-breeds. The total amount of polyunsaturated fatty acids in the examined milk for the two types of sheep was comparatively low with near concentrations (4.39-5.20%) in the period of the two years. The milk of the two groups had high values of the correlation SFA/PUSFA (15.71 and 13.17) and low values of PUSFA/SFA (0.06-0.08). Monоunsaturated fatty acids, represented mainly by the oleic acid (C18:1) varied during both periods from 21.92% to 25.32% and appeared as a substratum in the synthesis of CLA. The short-chain fatty acids (C4:0-C11:0) had higher values in Tzigay sheep in comparison with F2 cross-breeds of Chios. The long-chain fatty acids (C17iso-C25:0) maintained close concentration in the milk of Tzigay breed, while their content in the milk of F2 cross-breeds was increased.